Quarantined Within a New Colonial Order: The 1876-1877 Lake Winnipeg Smallpox Epidemic - Eyford, Ryan (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2006)
AbstractThis paper examines the link between the public health measures of quarantine and sanitation and the creation of racially-segregated reserves in the Canadian Northwest. In the fall of 1876, a smallpox epidemic broke out among Icelandic settlers and Aboriginal people living along the southwest coast of Lake Winnipeg. In response government officials formed a Board of Health and took measures to prevent the spread of the disease. The affected district was placed under a rigid quarantine and health officers were sent out to treat the victims and vaccinate people in adjacent communities. Due to both these measures and the diligence of local people, the disease was effectively contained and the number of dead, while significant, did not reach the levels of previous smallpox epidemics. However, the public health response to the crisis had far reaching consequences. By extending and legitimating the authority of the Canadian state over a region where its influence was previously quite limited, quarantine and sanitation helped reify a new colonial order mandating the compartmentalization of land and people into a system of Indian and immigrant reservations.